Business Data Processing Systems / Second Edition - Orilia Lawrence S; Stern Nancy; Stern Robert (John Wiley & Sons)
This book is designed for students and professional people overseas. It is an unabridged reprinting of the original hardbound edition. Preface, Introduction to Systems Concepts, Systems Studies - An Overview, The System Analyst, Fundamental Concepts of Analysis and Design, Basic Design Considerations, Form Design, Card Design, Design of High-Level Files, Systems Flowcharts and Decision Tables, Information Processing, Hardware, Data Communications, Management Information Systems, Project Controls and Management, Controls and Feedback, Analysis of Systems Cost, Feasibility Studies, Planning Tools, The Systems Package, Problem Definition and Systems Documentation, Case Study - Personnel, Case Study - Accounts Receivable, Characteristics of Selected Computer Systems, Index.